Fabrication of a biodegradable scaffold with localized response to bacterial infections - Hassanbhai, Ammar M. (2020)
Implant-associated infections remain a significant source of morbidity in the clinic. Systemic administration of antibiotics is often ineffective, due in part to limited vascularization of the implant site. Here, we describe a physical method of incorporating antibiotics into biodegradable scaffolds. Antibiotics gentamicin sulfate (GS) and metronidazole (MZ) were cryomilled with polycaprolactone (PCL) and subsequently heat-melded. Antibiotic-loaded films were evaluated for mechanical properties, drug release characteristics, anti-microbial efficacy and cytotoxicity. Our results suggest this process to be feasible for the generation of thin film coatings with varying drug concentrations. Release profiles indicated an initial burst release for both antibiotics with a sustained release of 3 and 8 days for GS and MZ films respectively. The films inhibited bacterial growth, while viability assays suggest low mammalian cytotoxicity. Taken together, these findings establish this method as a chemical-free means to form biodegradable drug scaffolds for the tailored local delivery of antibiotics.